2018
DOI: 10.1155/2018/5326340
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Implant Bone Resorption during Healing Abutment Placement: The Effect of a 0.20% Chlorhexidine Gel vs. Placebo—A Randomized Double Blind Controlled Human Study

Abstract: Introduction Peri-implant marginal bone loss (MBL) seems to be more pronounced in the first year of loading despite all the studies and changes implemented to reduce it. Among the different causes, the presence of a microgap makes the interface between fixture and abutment colonizable by bacteria, causing an inflammatory response and consequent bone resorption. To reduce this several local antiseptics like chlorhexidine digluconate (CHX) were used after surgical procedures. Aim The objective was to radiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…To reduce this bone tissue loss, a number of researchers have used similar techniques to those in this study, and obtained comparable results, indicating the promise of this approach. Sinjari et al used chlorhexidine digluconate as a gel, compared against a placebo. The results showed that applied medication significantly reduced bone loss in the first year of using implant‐supported prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce this bone tissue loss, a number of researchers have used similar techniques to those in this study, and obtained comparable results, indicating the promise of this approach. Sinjari et al used chlorhexidine digluconate as a gel, compared against a placebo. The results showed that applied medication significantly reduced bone loss in the first year of using implant‐supported prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…All patients gave a written informed consent to the treatment and study recruiting. The trial was registered on clinicaltrials.gov with registration number NCT03431766 as previously described [32]. This article was written following the CONSORT statement for improving the quality of randomized controlled trials, RCTs (Figure 1) [37].…”
Section: Study Design Patient Selection and Randomizationmentioning
confidence: 99%
“…The stages of the study were organized as follows: T0, first surgical stage: implant placement, recording of clinical data and collection of soft tissue biopsies for immunohistochemical analysis (baseline); T1, second surgical stage after 8 weeks: recording of clinical data and collection of soft tissue biopsies for immunohistochemical analysis and insertion of healing abutment; T2, first prosthetic stage (implant impression) at 10 weeks: healing abutment collection for microbiological analysis (for more details see Table 1). The primary outcome of this Randomized Clinical Trial (RCT) was to analyze the marginal bone resorption around dental implants as previously described in details [32]. Meanwhile, the objective of the present paper (the secondary outcome of the RCT) was to investigate by means of a quantitative analysis, the presence of P. gingivalis on the healing abutment when 0.20% CHX gel (Plak Gel; Polifarma Wellness Srl, Rome, Italy) and placebo gel (Placebo, Polifarma Wellness Srl, Rome, Italy) were applied during the first and second surgical stages.…”
Section: Study Design Patient Selection and Randomizationmentioning
confidence: 99%
See 2 more Smart Citations